Caries Risk Assessment Using the "CARA" Application in Students of Candijati 01 Elementary School in Jember - Prihatiningrum, Berlian; Probosari, Niken; Sulistiyani, Sulistiyani; Rahadrjo, Roedy Budi; Setyorini, Dyah (Odonto : Dental Journal, 2024)
Background: The key to successful treatment to prevent dental caries in children is accuracy in determining the risk factors that cause dental caries. Caries risk is a person's chance of having several caries lesions over a certain period of time. Measuring the risk of caries is carried out so that preventive measures can be directed directly at people who have a higher risk of cariesMethod: Research used is analytical observational with a cross sectional approach. The total population in this study were 170 students aged 6-12 years at Candijati 01 Elementary School. The results of filling out the questionnaire by respondent, dietary survey sheet and also a clinical examination of the oral cavity will be entered into the CARA application to obtain caries risk level for each individual and will display all data in a bar chart.Result: Based on this study, 53,5% students in Candijati 01 elementary School is low caries risk. Based on the indicators used in the CARA application, the results showed that caries indicators and dental treatment history play an important role in causing dental caries. Meanwhile, dental health indicators act as predisposing factors for dental caries.Conclusion: Based on the CARA analysis found that 6-12 years old students of Candijati 01 Elementary School who had were at a low risk category, but still having medium potential of avoiding new caries occurrence by controlling risk factors. CARA Application can be used as caries risk assessment because this application is easy to use and simple